The application of stochastic design strategies to primitive and complex shapes - Groth, Jan-Hendrik (2023)
Corporations and research institutes increasingly adopt Additive Manufacturing (AM) as a complementary manufacturing process, which enables them to manufacture parts or components that either cannot be manufactured from Traditional Manufacturing (TM) processes or the cost is significantly lower. This adoption process involves rethinking design strategies to leverage the full potential of AM, namely the design of highly complex and customised parts. Inevitably, intelligent design strategies will lead to increased part or equipment performance. This raises competitiveness over companies that do not efficiently apply these design strategies. One of these design strategies is cellular material design, which is an essential part of this thesis and will be explained. Cellular material design is considered a design strategy of Biomimicry. Biomimicry assumes that natural designs provide an acceptable solution for applications such as thermal devices, body armour, etc.